Analisis Pengaruh Rasio Keuangan Terhadap Harga Saham Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (Studi Kasus Padaperusahaan Mining And Mining Service) 2012-2014 - Nurcahyo, Galuh Asri; , Dra. Chuzaimah, M.M (2016)
This research aims to determine whether the variable Current Ratio, Return on Assets, Total Asset Turnover, Price Earning Ratio, da Earning Per Share individually and jointly affect to the price of shares in the mining and mining services company which listed on Indonesian Stock Exchange period 2012 -2014.Data source which has been used are secondary data from the financial statements of mining and mining company service issued by the Indonesian Capital Market Directory (ICMD). The population which has been used is the mining and mining services company which registered on the Indonesia Stock Exchange 2012-2014 period as many as 42 companies. The samples selected by purposive sampling, obtained sample of 17 companies. Technical analysis has been regression test. The results of the measurement of F test shows that the Current Ratio, Total Asset Turnover, Return On Assets, Earning Per Share and Price Earning Ratio jointly significant effect on stock prices from the measurement of the t test variable Current Ratio, Total Asset Turnover, Price Earning ratio and Earning Per Share significant effect on the stock prices on mining and mining service companies. While the Return On Assets not significantly influence to the stock prices. In the mining and mining services company which registered on the Indonesian Stock Exchange 2012-2014 period.